Implementation of Information Technology in School Administration Management: A Case Study at Regina Pacis Bajawa Private High School - Yohanes Podhi Ngey (Green Publisher Indonesia, 2024)
This research aim to develop theoretical prepositions the implementation of information technology in school administration, focusing on a case study at the Regina Pacis Bajawa Private High School. The study employs a qualitative research approach, specifically using a case study method, to explore, explain, and describe the implementation of information systems in school administration. The research emphasizes the importance of technology in improving the quality of education and the efficiency of administrative processes. It delves into the vision and mission of the school, the use of various technology-based applications and websites, and the indicators for achieving effective school management. The implementation of information technology in school administration, specifically at Regina Pacis Bajawa Private High School, has positively impacted the delivery of information, ensuring speed, accuracy, and quality. Despite challenges in implementing management information systems, the commitment to enhancing educational services and teachers' utilization of technology remains high. The importance of information technology in education is increasingly evident, emphasizing the need for ongoing optimization of management information systems. This research highlights the crucial role of structured learning information systems and effective management systems in improving education quality. It stresses the involvement of all stakeholders, particularly school principals and teachers, in successful curriculum implementation. Overall, the implementation of information technology has significantly improved educational services, and continuous efforts are essential to enhance management information systems for high-quality education.